FKBP5 expression in human adipose tissue: potential role in glucose and lipid metabolism, adipogenesis and type 2 diabetes - Sidibeh, Cherno O.; Pereira, Maria J.; Abalo, Xesus M.; J. Boersma, Gretha; Skrtic, Stanko; Lundkvist, Per; Katsogiannos, Petros; Hausch, Felix; Castillejo-López, Casimiro; Eriksson, Jan W. (Endocrine, 2018)
Purpose Here, we explore the involvement of FKBP51 in glucocorticoid-induced insulin resistance (IR) in human subcutaneous adipose tissue (SAT), including its potential role in type 2 diabetes (T2D). Moreover, we assess the metabolic effects of reducing the activity of FKBP51 using the specific inhibitor SAFit1. Methods Human SAT was obtained by needle biopsies of the lower abdominal region. FKBP5 gene expression was assessed in fresh SAT explants from a cohort of 20 T2D subjects group-wise matched by gender, age and BMI to 20 non-diabetic subjects. In addition, human SAT was obtained from non-diabetic volunteers (20F/9M). SAT was incubated for 24 h with or without the synthetic glucocorticoid dexamethasone and SAFit1. Incubated SAT was used to measure the glucose uptake rate in isolated adipocytes. Results FKBP5 gene expression levels in SAT positively correlated with several indices of IR as well as glucose area under the curve during oral glucose tolerance test ( r = 0.33, p < 0.05). FKBP5 gene expression levels tended to be higher in T2D subjects compared to non-diabetic subjects ( p = 0.088). Moreover, FKBP5 gene expression levels were found to inversely correlate with lipolytic, lipogenic and adipogenic genes. SAFit1 partly prevented the inhibitory effects of dexamethasone on glucose uptake. Conclusions FKBP5 gene expression in human SAT tends to be increased in T2D subjects and is related to elevated glucose levels. Moreover, FKBP5 gene expression is inversely associated with the expression of lipolytic, lipogenic and adipogenic genes. SAFit1 can partly prevent glucose uptake impairment by glucocorticoids, suggesting that FKBP51 might be a key factor in glucocorticoid-induced IR.